Potassium-competitive acid blockers: state of the art - Augusto Urrego, José (2025)
Potassium-competitive acid blockers (PCABs) constitute an emerging class of drugs for the treatment of acid-related disorders. They represent an alternative to proton pump inhibitors (PPIs), which have been the standard therapy but present certain limitations. Currently, PCABs are available in Latin America and offer a promising therapeutic option. This review compares both drug classes across various key aspects. Potassium-competitive acid blockers (PCABs) offer significant advantages over proton pump inhibitors (PPIs) in terms of speed of action, potency, and duration of acid suppression, as well as efficacy in the treatment of erosive esophagitis and Helicobacter pylori eradication, among other aspects. Additionally, they exhibit lower interindividual variability. Currently, PCABs are available in Latin America and represent a promising therapeutic option. This review compares both drug classes across various key aspects.